The Analysis of University Students’ Syntaxis Errors in Constructing an English Paragraph - Putra, Octa Pratama (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study aims to analyse syntactic errors made by students at ABC University in English paragraph writing; specifically, those enrolled in English Literature and English Education programs. Although the population consisted of 30 students, the research focused on a sample of 10 student responses. A qualitative descriptive method was applied, using a case study approach to examine the students’ written texts in depth. The analysis identified various types of syntactic errors, including incorrect sentence structures, subject-verb agreement issues, and misplacement of modifiers, which are common challenges in academic writing for non-native English speakers. Each of the 10 student responses was carefully analysed and further developed with constructive feedback tailored to help students avoid similar mistakes in future academic writing tasks. The findings reveal not only recurring syntactic patterns that require attention but also highlight the importance of explicit instruction and practice in academic writing contexts. This study highlights the importance of continuous improvement in writing pedagogy to enhance students' syntactic accuracy and overall writing proficiency. Educators can use the insights gained to design more effective instructional strategies, ultimately aiming to support students in producing grammatically sound academic texts. Through targeted feedback and awareness-building, students are better equipped to develop their academic writing skills and minimize syntactic errors in future compositions.